MANAJEMEN MUTU PENDIDIKAN DI SMA-IT INSAN MULIA BOARDING SCHOOL (IMBOS) PRINGSEWU - Taufik Hidayat; Mega Silvia Dewi; Junaidah Junaidah; Ahmad Fauzan (Jurnal Manajemen Pendidikan, 2025)
Educational quality is one of the important factors that determine student learning success and school progress. SMA IT IMBOS Pringsewu, as an integrated Islamic school, strives to continuously improve its educational quality. This study focuses on how SMA IT IMBOS Pringsewu implements educational quality management through the PDCA stages. This study uses a qualitative approach with a case study method. Data were obtained through interviews with the principal, curriculum vice-chancellor, student affairs vice-chancellor, teachers, as well as documentation and direct observation. Data were analyzed descriptively to describe how the quality management process is carried out in the school. The results show that at the Plan stage, the school has developed a vision, mission, quality policy, success indicators, and a strategic plan developed through deliberation with the management team. At the Do stage, implementation is carried out through strengthening a quality culture among teachers and staff, professional training, and implementing student-oriented learning. At the Check stage, the school routinely monitors teacher and staff performance, uses student learning outcome data, and conducts internal quality audits and stakeholder satisfaction evaluations. Meanwhile, at the Act stage, the school carries out follow-up actions by revising strategies and SOPs, implementing systemic changes, rewarding good practices, and disseminating best practices to ensure the quality culture continues to develop.